PENGARUH KEPERCAYAAN DAN KEPUASAN TERHADAP LOYALITAS NASABAH BANK SYARIAH INDONESIA - Margaretha Ardhanari; Sebastiana Viphindrartin (Jurnal Istiqro, 2022)
The study aims to test the effect of trust and satisfaction on both partially or simultaneously on customer loyalty of Indonesian Syariah Bank. This study used a sample of 100 Indonesian Islamic Bank customers with purposive sampling technique. Data analysis used multiple linear regression. The results showed that trust (X1) partially had a positive and significant effect on customer loyalty (Y) as evidenced by the results of the t-statistical value of 8.294 with a significance value of 0.000 <0.05. The satisfaction (X2) has a t-statistic value of 2.578 with a significance value of 0.011 <0.05, thus the satisfaction (X2) has a positive and significant influence on customer loyalty (Y). The results of the F test with a statistical F value of 205.699 with a significance of 0.000. These results prove that trust and satisfaction simultaneously have a positive and significant influence on customer loyalty